2018
DOI: 10.1002/ldr.3009
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impacts of shrub plantations in a desert–oasis ecotone: Accumulation of soil nutrients, salinity, and development of herbaceour layer

Abstract: This study used a 40‐year chronosequence of Haloxylon ammodendron plantations to evaluate its impacts on soil and vegetation conditions in a desert–oasis ecotone with extremely low annual precipitation (≈100 mm). We found that the fraction of silt and clay contents significantly increased from 6.4% and 5.1% in Year 0 to 22–23.3% and 15.8–18% in the 40‐year‐old plantation in the soil depths of 0–10 and 10–20 cm, respectively. Soil nutrients (i.e., soil organic matter, total nitrogen, and total phosphorus) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…To fix sand dune and combat desertification, H. ammodendron , C. mongolicum , and other shrub species have been widely used in afforestation in the drylands of northwestern China (Yu & Wang, ). Though some considered H. ammodendron a better afforestation species than C. mongolicum due to its stronger drought tolerance (Xu, Ji, Jin, & Zhang, ; Yao, Yan, & Yang, ), our prediction result showed that the suitable habitat of H. ammodendron may contract substantially in the Junggar Basin, while the suitable habitat of C. mongolicum is likely to expand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To fix sand dune and combat desertification, H. ammodendron , C. mongolicum , and other shrub species have been widely used in afforestation in the drylands of northwestern China (Yu & Wang, ). Though some considered H. ammodendron a better afforestation species than C. mongolicum due to its stronger drought tolerance (Xu, Ji, Jin, & Zhang, ; Yao, Yan, & Yang, ), our prediction result showed that the suitable habitat of H. ammodendron may contract substantially in the Junggar Basin, while the suitable habitat of C. mongolicum is likely to expand.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, vegetation coverage reduction and degradation driven by climate change and overexploitation of water resources have been observed (Wang, Pan, Wang, Shen, & Lu, ). On the other hand, several drought‐resistant woody plant species have been widely planted since 1970s as large‐scale afforestation efforts to combat desertification in the drylands of northwestern China (Yu & Wang, ). Nevertheless, these efforts are not always successful due to a lack of understanding about the habitat suitability of the planted species and their responses to climatic change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study remarks that the implementation of action plans for land remediation needs to consider social aspects and the implications for long-term sustainability. An increasing number of studies are showing the importance of long-term monitoring in restoration (Shackelford et al, 2018), as vegetation establishment and soil properties can go through transient states over time and may evolve over decades (Yu & Wang, 2018). At landscape scales, geomorphic analysis and remote sensing techniques provide sensitive satellite-derived indices that can offer multiple possibilities for monitoring studies at such large ranges.…”
mentioning
confidence: 99%
“…Revegetation efforts generally result in improvement of soil fertility and enhancement of ecosystem services and functions such as carbon sequestration (Gao, Dang, Zhao, Liu, & Liu, 2018), nutrient cycling (Barliza, Peláez, & Campo, 2018;Hu et al, 2018), and soil microbial diversity and activity (Garcia et al, 2018;Liu et al, 2019); nevertheless, it can also lead to adverse effects such as salinity which may affect the success of restoration efforts in the long term (Yu & Wang, 2018) and generally increases plant productivity and carbon sequestration in the medium or long-term, as highlighted by Valdecantos and Fuentes (2018). Also in this issue, Luna, Vignozzi, Miralles, and Solé-Benet (2018) show that woodchip mulch can be effective for trapping runoff and sediment in mine rehabilitation sites, whereas organic amendments formed by composted waste can improve infiltration and reduce water erosion (Figure 2).…”
mentioning
confidence: 99%